Stochastic Enhancement of High-order Harmonic Generation - YAVUZ, İLHAN (IOP PUBLISHING LTD, 2012)
Here we demonstrate that from the combination of fundamental laser and noise it is possible to enhance harmonic intensities by 5 orders of magnitude with a modest noise-to-laser amplitude ratio.